Analysis of the Relationship Between Emotional Intelligence and the Motivation of Extracurricular Futsal Students to Middle School - Usman, Arifuddin; Pratama, Muh. Rama; Arimbi, Arimbi (ETDC: Indonesian Journal of Research and Educational Review, 2025)
Psychological factors like emotional intelligence influence kids' willingness to exercise, especially in extracurricular sports like futsal. Schools must understand the non-technical aspects that affect student involvement and exercise quality to build more successful and sustainable coaching programs. This study aims to analyze the relationship between emotional intelligence and exercise motivation in futsal extracurricular students at middle school. The study used a quantitative approach with a correlational design. The study population was all 50 extracurricular participants, with a sample of 25 boys and 25 girls selected through a purposive sampling technique at Middle School 27 Makassar. Emotional intelligence data were collected using a questionnaire structured based on indicators of self-awareness, self-regulation, motivation, empathy, and social skills, while exercise motivation data were obtained through a questionnaire based on intrinsic and extrinsic motivation aspects. The data collection technique was carried out through a structured survey, and all instruments have undergone validity and reliability tests. Data analysis used Pearson Product Moment correlation to test the relationship between the two variables. The results of the study showed a positive and significant relationship between emotional intelligence and students' motivation to practice, meaning that the higher a student's emotional intelligence, the higher their motivation to participate in futsal training. This finding indicates the need for a coaching program that focuses not only on technical skills but also on strengthening students' emotional aspects. The study's conclusion confirms that emotional intelligence is an important predictor in increasing students' motivation to practice in extracurricular futsal activities.